The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/sym13040706
|View full text |Cite
|
Sign up to set email alerts
|

X-SDD: A New Benchmark for Hot Rolled Steel Strip Surface Defects Detection

Abstract: It is important to accurately classify the defects in hot rolled steel strip since the detection of defects in hot rolled steel strip is closely related to the quality of the final product. The lack of actual hot-rolled strip defect data sets currently limits further research on the classification of hot-rolled strip defects to some extent. In real production, the convolutional neural network (CNN)-based algorithm has some difficulties, for example, the algorithm is not particularly accurate in classifying som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 39 publications
(48 reference statements)
0
42
0
Order By: Relevance
“…In the next work, we may verify through more experiments which combination of this scheme and which model will achieve optimal results. Although our previous paper [7] showed that a RepVGG based scheme with an added attention mechanism may be superior in terms of effectiveness; according to Table 3, the ResNet50 based approach has an advantage over RepVGG in terms of number of parameters and computational complexity, i.e., it is easier to deploy in practice.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the next work, we may verify through more experiments which combination of this scheme and which model will achieve optimal results. Although our previous paper [7] showed that a RepVGG based scheme with an added attention mechanism may be superior in terms of effectiveness; according to Table 3, the ResNet50 based approach has an advantage over RepVGG in terms of number of parameters and computational complexity, i.e., it is easier to deploy in practice.…”
Section: Discussionmentioning
confidence: 97%
“…With the definition of channel attention and DCT, we can summarize two points: (1) Existing methods use GAP as preprocessing when doing channel attention. (2) DCT can be viewed as a weighted sum of inputs, and the weights are the cosine part of Equations ( 6) and (7). For more details, please refer to the reference [29].…”
Section: Introduction Of Fcanetmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, optical-digital control of the rolled strip surface is used in production [4,5]. However, new methods for obtaining and processing images have new requirements for detecting and localizing defects and determining their size, shape, and potential hazard, in order to identify which rolled strips should be rejected [6]. One of the problems is identifying and classifying a wide range of defects that are similar in their geometry [7].…”
Section: Introductionmentioning
confidence: 99%